Adaptive evolution of West Nile virus facilitated increased transmissibility and prevalence in New York State. Issue 1 (31st December 2022) - Bialosuknia, Sean M.; Dupuis II, Alan P.; Zink, Steven D.; Koetzner, Cheri A.; Maffei, Joseph G.; Owen, Jennifer C.; Landwerlen, Hannah; Kramer, Laura D.; Ciota, Alexander T.
ABSTRACT: West Nile virus (WNV; Flavivirus, Flaviviridae) was introduced to New York State (NYS) in 1999 and rapidly expanded its range through the continental United States (US). Apart from the displacement of the introductory NY99 genotype with the WN02 genotype, there has been little evidence of adaptive evolution of WNV in the US. WNV NY10, characterized by shared amino acid substitutions R1331K and I2513M, emerged in 2010 coincident with increased WNV cases in humans and prevalence in mosquitoes. Previous studies demonstrated an increase in frequency of NY10 strains in NYS and evidence of positive selection. Here, we present updated surveillance and sequencing data for WNV in NYS and investigate if NY10 genotype strains are associated with phenotypic change consistent with an adaptive advantage. Results confirm a significant increase in prevalence in mosquitoes though 2018, and updated sequencing demonstrates a continued dominance of NY10. We evaluated NY10 strains in Culex pipiens mosquitoes to assess vector competence and found that the NY10 genotype is associated with both increased infectivity and transmissibility. Experimental infection of American robins ( Turdus migratorius ) was additionally completed to assess viremia kinetics of NY10 relative to WN02. Modelling the increased infectivity and transmissibility of the NY10 strains together with strain-specific viremia demonstrates a mechanistic basis for selection that has likely contributed to the increased prevalence of WNV in NYS.